Answers

The Brainliest Answer!
2015-07-20T21:39:45+05:30
Let the two numbers be 'x' , 'y' ,
Given  x+y = 120 -------(1) 
           x-y  = -22 --------(2)
Now,(1)+(2) = x+y = 120 
                (+) x-y  =  -22
⇒2x = 98
 ⇒ x = 98/2 = 49
 Now , from (1) x + y = 120 
⇒49+y = 120
 ⇒y = 120-49 = 71 
 Therefore , the two numbers are 49 and 71 .            
2 5 2
2015-07-20T22:04:23+05:30
Let the two numbers be 'x' and 'y' namely 
now from the data given
x+y=120 ...........(1)
and
x-y= -22.........(2)
now let s do this by elemenation method
(1)+(2)
x+y=120
x-y= -22
here  +y and -y get canceled 
therefore 2x=98
⇒x=98/2
therefore x= 49
now as we know what is x let us substitute this value in equation (1)
x+y=120
49+y=120
y=120-49
y=71.
therefore the numbers are 49 and 71



1 5 1
please mark it as the best
thank you so much
ur welcome